East/Central/South African Genotype in a Chikungunya Outbreak, Dhaka, Bangladesh, 2017 - Mizanur Rahman (Emerging Infectious Diseases, 2019)
In 2017, an unprecedented increase in febrile illness was observed in Dhaka, Bangladesh. Real-time reverse transcription PCR confirmed that 603 (40.2%) of 1,500 cases were chikungunya fever. Phylogenetic analysis revealed circulation of the non-A226V East/Central/South African genotype of chikungunya virus in Bangladesh.